2021
DOI: 10.1186/s12967-021-02876-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene alterations as predictors of radiation-induced toxicity in head and neck squamous cell carcinoma

Abstract: Background Optimizing the therapeutic ratio for radiation therapy (RT) in head and neck squamous cell carcinoma (HNSCC) is uniquely challenging owing to high rates of early and late toxicity involving nearby organs at risk. These toxicities have a profound impact on treatment compliance and quality of life. Emerging evidence suggests that RT dose alone cannot fully account for the variable severity of RT-related adverse events (rtAEs) observed in HNSCC patients. Next-generation sequencing has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
9
0
2
Order By: Relevance
“…Our results indicate HPV-negative status or having an oropharyngeal cancer may increase a patient's risk of high-grade late dysphagia. Recent studies have shown that the genomics of the primary tumor can have an effect on normal tissue outcomes [18]. Thus, the relationship seen here between cancer type and worsened outcomes may be due to underlying genetics of the tumor effecting the micro-environment though more analysis is needed to evaluate the cause of this effect.…”
Section: Discussionmentioning
confidence: 90%
“…Our results indicate HPV-negative status or having an oropharyngeal cancer may increase a patient's risk of high-grade late dysphagia. Recent studies have shown that the genomics of the primary tumor can have an effect on normal tissue outcomes [18]. Thus, the relationship seen here between cancer type and worsened outcomes may be due to underlying genetics of the tumor effecting the micro-environment though more analysis is needed to evaluate the cause of this effect.…”
Section: Discussionmentioning
confidence: 90%
“…( 10 ) reported that simvastatin could reverse RILI-associated dysregulated gene expression including TP53. Genetic alterations in NOTCH1 were associated with a high mean grade of radiation-induced toxicity in head and neck squamous cell carcinoma ( 56 ). SIRT1 has a protective effect against radiation injury ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the SPTA1 gene cause various inherited erythroid disorders, 53 including elliptocytosis type 2, pyrexia, and spherocytic hemolytic anemia. 54,55 In recent years, the SPTA1 gene has been reported in squamous lung cancer, 56 head-and-neck squamous cell carcinoma, 57 spinal muscular atrophy, 58 risk and diagnosis of type 2 diabetes, 59 brain metastases and primary tumors, 60 and prostate cancer syndrome, 61 and studies about converting immortalized human erythroid cell lines into in vitro manufactured erythrocytes. 62 Transcriptome analysis showed that SPTA1 gene is enriched in the apoptotic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%